2010
DOI: 10.5194/acp-10-7963-2010
|View full text |Cite
|
Sign up to set email alerts
|

Modelling surface ozone during the 2003 heat-wave in the UK

Abstract: Abstract. The EMEP4UK modelling system is a high resolution (5×5 km 2 ) application of the EMEP chemistrytransport model, designed for scientific and policy studies in the UK. We demonstrate the use and performance of the EMEP4UK system through the study of ground-level ozone (O 3 ) during the extreme August 2003 heat-wave. Meteorology is generated by the Weather Research and Forecast (WRF) model, nudged every six hours with reanalysis data. We focus on SE England, where hourly average O 3 reached up to 140 pp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
149
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 181 publications
(163 citation statements)
references
References 40 publications
6
149
0
1
Order By: Relevance
“…Land use categories were based on the MODIS IGBP classification. This WRF configuration is similar to that discussed in Vieno et al (2010), where it is shown to perform well in comparison with measurements. An evaluation of the WRF-EMEP4UK modelling system against measured gaseous and particulate pollutant concentrations across the UK for 2001 to 2010 is given by Lin et al (2017), while Ots et al (2016) compares WRF-EMEP4UK air quality simulations with detailed measurements of secondary organic aerosols made in London during the 2012 ClearfLo campaign.…”
Section: Regional-scale Modelling: Emep4uksupporting
confidence: 60%
See 2 more Smart Citations
“…Land use categories were based on the MODIS IGBP classification. This WRF configuration is similar to that discussed in Vieno et al (2010), where it is shown to perform well in comparison with measurements. An evaluation of the WRF-EMEP4UK modelling system against measured gaseous and particulate pollutant concentrations across the UK for 2001 to 2010 is given by Lin et al (2017), while Ots et al (2016) compares WRF-EMEP4UK air quality simulations with detailed measurements of secondary organic aerosols made in London during the 2012 ClearfLo campaign.…”
Section: Regional-scale Modelling: Emep4uksupporting
confidence: 60%
“…2. An intermediate 10 km × 10 km resolution domain is used for WRF (Weather Research and Forecasting Model) to ensure numerical stability, but is not required for the chemistry transport calculations (Vieno et al, 2010). Full details of the WRF model domains are given in Table A1.…”
Section: Regional-scale Modelling: Emep4ukmentioning
confidence: 99%
See 1 more Smart Citation
“…Meteorology also plays a large role in local-scale ozone concentration affecting deposition and transport (e.g. Vieno et al, 2010;Francis et al, 2011) alongside transport and dispersion in urban Figure 28. In a continental chemistry transport simulation with the CHIMERE model at a resolution of 8 km, major urban centres in northern and central Europe highlight the NO x titration process (left: summertime average of daily maximum ozone), while the total oxidant level (right: O 3 as NO 2 + O 3 , annual mean) is high in most European cities (adapted from Terrenoire et al, 2015).…”
Section: Atmosmentioning
confidence: 99%
“…The system is similar to the EMEP4UK modelling system (Vieno et al, 2010) which is designed for scientific and policy studies in the UK at 5-km horizontal resolution. A detailed description of the configuration of NILU''s WRF--EMEP model system is given in Karl et al (2014).…”
Section: Elsevier_stoten_17722mentioning
confidence: 99%